A rare case of suicide by gunshot with nasal entry assessed by classical autopsy,post-mortem computed tomography(PMCT) and post-mortem magnetic resonance imaging(PMMR) - Abdul Rashid, Saiful Nizam; Martinez, Rosa Maria; Ampanozi, Garyfalia; Thali, Michael J.; Bartsch, Christine (Elsevier, 2013)
Determination of the manner of death in cases of gunshot injuries can be very challenging. The weapon, gunshot residues, blood spatters, fingerprints and DNA evidence are crucial in solving these cases. The presence of an entry wound at an unusual site could create interpretation problems. This is complicated further by atypical wound morphology. It is a well-known fact that the right temporal, mouth, forehead, submental and parietal regions are the typical entrance wound sites for suicide with firearms to the head. Suicidal shooting through the nose is extremely rare. In cases of suicide by firearms some useful points are the site of entry wound, the direction of the internal projectile path and the circumstances of death. PMCT and PMMR clearly showed the projectile, wound tract and damage to the bones and brain tissues prior to autopsy. PMMR also demonstrated the pyramidal tract edema caused by pressure shock waves from the projectile. This finding was reported in living patients who survived gunshot injuries to the head but has never been reported in PMMR. We demonstrate these points in a case of a suicidal gunshot through the nose assessed by classical autopsy, PMCT and PMMR.